The indispensable PC Hardware book - Hans-Peter Messmer (Addison-Wesley, 1997)
The book is divided into six major parts. Part 1 introduces the subject of personal computer hardware. Part 2 presents the motherboard components. Part 3 introduces the various PC architectures. Part 4 provides extensive information about the support chips present in all PCs. Part 5 is delicated to mass storage. Part 6 presents interfaces, keyboards and mice as well as modern graphics adapters and multimedia. The appendices provide a lot of practical information. Finally, the Glossary is a small but nevertheless comprehensive computer encyclopedia which explains most terms and concepts related to personal computer hardware